2017
DOI: 10.1155/2017/7167691
|View full text |Cite
|
Sign up to set email alerts
|

Combined Docking with Classical Force Field and Quantum Chemical Semiempirical Method PM7

Abstract: Results of the combined use of the classical force field and the recent quantum chemical PM7 method for docking are presented. Initially the gridless docking of a flexible low molecular weight ligand into the rigid target protein is performed with the energy function calculated in the MMFF94 force field with implicit water solvent in the PCM model. Among several hundred thousand local minima, which are found in the docking procedure, about eight thousand lowest energy minima are chosen and then energies of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 32 publications
0
27
0
6
Order By: Relevance
“…The time requirements were thus reduced from days to tens of minutes, which makes the SQM/COSMO SF applicable to drug design even in an industrial context. It was demonstrated that the SQM/COSMO SF outperformed standard SFs at the PM6‐D3H4X and DFTB3‐D3H4X (for Zinc metalloproteins) levels in identifying the native binding pose, which is a critical prerequisite for affinity estimation in physics‐based scoring . However, it was not clear whether the simplified SQM/COSMO SF could reliably estimate P‐L binding affinities and provide the valuable ranking for an inhibitor series.…”
Section: Introductionmentioning
confidence: 99%
“…The time requirements were thus reduced from days to tens of minutes, which makes the SQM/COSMO SF applicable to drug design even in an industrial context. It was demonstrated that the SQM/COSMO SF outperformed standard SFs at the PM6‐D3H4X and DFTB3‐D3H4X (for Zinc metalloproteins) levels in identifying the native binding pose, which is a critical prerequisite for affinity estimation in physics‐based scoring . However, it was not clear whether the simplified SQM/COSMO SF could reliably estimate P‐L binding affinities and provide the valuable ranking for an inhibitor series.…”
Section: Introductionmentioning
confidence: 99%
“…The 3888 trial structures were first optimized using the PM7 method (implemented in MOPAC program) leading to 648 local minima. However, some harmonic vibrational frequencies of the 648 conformers were imaginary.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Расширение применения суперкомпьютеров в данной области привело к формулировке так называемой процедуры квазидокинга [5,14,15], или докинга с комбинированным применением на первом шаге силового поля и на втором шаге другого силового поля или методов квантовой химии. В этой процедуре при докинге в заданном классическом силовом поле находят достаточно широкий спектр низкоэнергетических минимумов, а затем энергии этих минимумов пересчитывают в другом силовом поле или даже с помощью квантово-химических методов, и уже по пересчитанным значениям энергии определяют глобальный минимум и соответствующее ему наилучшее положение лиганда.…”
Section: Introductionunclassified
“…В этой процедуре при докинге в заданном классическом силовом поле находят достаточно широкий спектр низкоэнергетических минимумов, а затем энергии этих минимумов пересчитывают в другом силовом поле или даже с помощью квантово-химических методов, и уже по пересчитанным значениям энергии определяют глобальный минимум и соответствующее ему наилучшее положение лиганда. При таком подходе удалось показать [5,14,15], что наилучшие результаты по позиционированию лигандов достигаются при расчётах энергии комплекса белок-лиганд с помощью квантово-химического полуэмпирического метода PM7 [16] с учётом растворителя в модели COSMO [17]. Однако, в работах [14,15] на начальном шаге такой комбинированной процедуры докинга использовали сравнительно медленную версию программы FLM (версия 0.10), осуществляющую докинг с учётом растворителя в модели PCM (Polarized Continuum Model) [18].…”
Section: Introductionunclassified
See 1 more Smart Citation